1998
DOI: 10.4141/s97-009
|View full text |Cite
|
Sign up to set email alerts
|

Soil nitrogen and moisture as influenced by composts and inorganic fertilizer rate

Abstract: The addition of compost may mitigate soil degradation and contribute to the soil nutrient supply in spring cereal monoculture. A field study was carried out in eastern Quebec, Canada, to assess the impact of composts from four sources and ammonium nitrate (AN) applied at different rates in spring on soil moisture and inorganic N in spring wheat production (Triticum aestivum L. 'Messier'). The experiment was conducted in 1994 and 1995 on two different soils: a Kamouraska clay (Orthic Humic Gleysol) and a Saint-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
19
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 15 publications
5
19
0
Order By: Relevance
“…However, an increase in soil water content in DSPC-treated plots was not observed in 1997, suggesting that the presence of undecomposed material in the DSPC was responsible for this temporary increase. Similar shortterm effects were reported previously for raw de-inking paper sludges (Trépanier et al 1996;Aitken et al 1998;Simard et al 1998a), combined primary and secondary sludges (Cambouris et al 2000;Nemati et al 2000) and manure and commercial composts (Gagnon et al 1998). For personal use only.…”
Section: Soil Water Content and Phsupporting
confidence: 84%
“…However, an increase in soil water content in DSPC-treated plots was not observed in 1997, suggesting that the presence of undecomposed material in the DSPC was responsible for this temporary increase. Similar shortterm effects were reported previously for raw de-inking paper sludges (Trépanier et al 1996;Aitken et al 1998;Simard et al 1998a), combined primary and secondary sludges (Cambouris et al 2000;Nemati et al 2000) and manure and commercial composts (Gagnon et al 1998). For personal use only.…”
Section: Soil Water Content and Phsupporting
confidence: 84%
“…Based on a relationship between soil NO 3 -extracted by KCl and Nop, Bélanger et al (1998) concluded that conventional spring soil NO 3 -tests are inappropriate for predicting fertilizer N requirements of wheat in Atlantic Canada. Gagnon et al (1998), however, observed a close relationship between the soil profile inorganic N 30 d after N application and wheat N uptake at harvest. Accordingly, Zebarth and Paul (1996), recommended the use of a soil nitrate test in early to mid-June in order to determine if additional fertilizer N was required for silage corn produced in south coastal British Columbia (Canada).…”
Section: Economically Optimum N Fertilizer Ratementioning
confidence: 74%
“…In our case, the shorter period of treatment with mulches may have led to the type of mulch being more significant than the amount applied. Mulching with compost indicated a potential to improve N availability in soil [supported by Gagnon et al (1998)] and a trend towards an increase in total N content later in the season. This could be a result of mineralization of N compounds from the mulches and movement into the soil, as demonstrated by Havlin et al (1990) and Inbar et al (1993).…”
Section: Discussionmentioning
confidence: 99%